"It's called overamping": experiences of overdose among people who use methamphetamine - Robert W. Harding; Katherine T. Wagner; Phillip Fiuty; Krysti P. Smith; Kimberly Page; Karla D. Wagner (BMC, 2022)
Abstract Background The USA is experiencing increases in methamphetamine use and methamphetamine-related or attributed deaths. In the current study, we explore qualitative narratives of methamphetamine overdose and strategies used by people who use drugs to reduce the undesirable effects associated with methamphetamine use. Methods We conducted 21 qualitative interviews with people over the age of 18 who reported using methamphetamine in the previous 3 months in Nevada and New Mexico. Interviews were recorded, transcribed, and analyzed using qualitative thematic analysis. Results Respondents described a constellation of psychological and physical symptoms that they characterized as "overamping," experienced on a continuum from less to more severe. Reports of acute, fatal methamphetamine overdose were rare. Few reported seeking medical attention for undesirable effects (usually related to psychological effects). General self-care strategies such as sleeping and staying hydrated were discussed. Conclusions When asked directly, our respondents claimed that acute, fatal methamphetamine overdose is rare or even impossible. However, they described a number of undesirable symptoms associated with overconsumption of methamphetamine and had few clinical or harm reduction strategies at their disposal. Addressing this current wave of drug-related deaths will require attention to the multiple factors that structure experiences of methamphetamine "overdose," and a collaborative effort with PWUDs to devise effective harm reduction and treatment strategies.